Beyond the inhaled nitric oxide in persistent pulmonary hypertension of the newborn - Mei-Yin Lai; Shih-Ming Chu; Satyan Lakshminrusimha; Hung-Chih Lin (Pediatrics and Neonatology)
Persistent pulmonary hypertension (PPHN) is a consequence of failed pulmonary vascular transition at birth and leads to pulmonary hypertension with shunting of deoxygenated blood across the ductus arteriosus (DA) and foramen ovale (FO) resulting in severe hypoxemia, and it may eventually lead to life-threatening circulatory failure. PPHN is a serious event affecting both term and preterm infants in the neonatal intensive care unit. It is often associated with diseases such as congenital diaphragmatic hernia, meconium aspiration, sepsis, congenital pneumonia, birth asphyxia and respiratory distress syndrome. The diagnosis of PPHN should include echocardiographic evidence of increased pulmonary pressure, with demonstrable right-to-left shunt across the DA or FO, and the absence of cyanotic heart diseases. The mainstay therapy of PPHN includes treatment of underlying causes, maintenance of adequate systemic blood pressure, optimized ventilator support for lung recruitment and alveolar ventilation, and pharmacologic measures to increase pulmonary vasodilation and decrease pulmonary vascular resistance. Inhaled nitric oxide has been proved to treat PPHN successfully with improved oxygenation in 60–70% of patients and to significantly reduce the need for extracorporeal membrane oxygenation (ECMO). About 14%–46% of the survivors develop long-term impairments such as hearing deficits, chronic lung disease, cerebral palsy and other neurodevelopmental disabilities.